2022
DOI: 10.26552/com.c.2022.2.d72-d84
|View full text |Cite
|
Sign up to set email alerts
|

Causes for the Change Orders in Road Construction: Reviewed from Owner

Abstract: Changes in road construction are affected by the owner and contractor at the beginning, middle, or end of the project. This study aims to determine the ranking of the factors that cause change orders for road construction from the owner's point of view. Data was collected by distributing questionnaires and interviews to project owners. Reliability and validity tests involving 32 respondents resulted in 48 causes of change orders. This study quantifies the relative importance of the factors that cause change or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…• Obtained the highest rank from 5 categories that affect the occurrence of Cost Overrun in construction projects during the COVID-19 pandemic based on categories is The Estimated Cost with a RII value of 0.811 and the smallest is Others with a RII value of 0.561 • From a total of 20 factors that have been compiled during the study, the results of 13 factors can be used because they passed the validation and reliability tests. From the results of the RII calculation, 2 factors were obtained that have a very high level of importance that affect the occurence of cost overrun in construction projects during the COVID-19 pandemic, namely:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Obtained the highest rank from 5 categories that affect the occurrence of Cost Overrun in construction projects during the COVID-19 pandemic based on categories is The Estimated Cost with a RII value of 0.811 and the smallest is Others with a RII value of 0.561 • From a total of 20 factors that have been compiled during the study, the results of 13 factors can be used because they passed the validation and reliability tests. From the results of the RII calculation, 2 factors were obtained that have a very high level of importance that affect the occurence of cost overrun in construction projects during the COVID-19 pandemic, namely:…”
Section: Discussionmentioning
confidence: 99%
“…The RII method is used to measure the relative importance of the causes of the change sequence factor. These results show the rating of factors and groups according to their level of importance in relation to the causes of the order of change [13]. Before processing data to find the level of importance, the data must first be followed for feasibility using validity tests and reliability tests.…”
Section: Methods Of Analysis and Data Processingmentioning
confidence: 99%
“…For instance, Yap et al [31] identified a lack of coordination among consultants as being one of the most critical factors causing design changes. Similarly, in a different project setting, i.e., road construction, Waty, and Sulistio [32] found that coordination among contracting stakeholders is among the top causes of change orders. The lack of communication can arise because of organizational and/or bureaucracy-based issues, which is another subcategory of project management.…”
Section: Implications Of Findings For Project Managementmentioning
confidence: 97%
“…Kemudian dengan menggunakan Relative Importance Index akan diperoleh tingkat kepentingan relatif dari penyebab faktor urutan perubahan. Hasil yang diperoleh akan menunjukkan peringkat faktor dan kelompok sesuai dengan tingkat kepentingan mereka berdasarkan kaitannya dengan penyebab change order (Waty & Sulistio, 2021).…”
unclassified